NUMBER OF KHAMIR IN BALI CATTLE RUMEN VIEWED FROM pH AND BODY WEIGHT - Widyaningtyas, Ike Siwi; Besung, I Nengah Kerta; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana; Vol. 14 No. 5 October 2022DO - 10.24843/bulvet.2022.v14.i05.p03, 2022)
This study aims to determine the amount of yeast, rumen pH, and body weight of bali cattle. 17 samples were taken from the rumen fluid of bali cattle. This study was an analytic observational study with a cross sectional approach with observations on the number of yeast on rumen pH and body weight of bali cattle. The data obtained are then presented descriptively followed by regression correlation analysis. The results showed the average number of yeast in the rumen of bali cattle 21x10 3 ± 6.9x10 3 cells/ml, the average pH of rumen fluid of bali cattle 6.9 ± 0.07, and the average body weight of bali cattle 251 ± 47.8 kg. There is a significant difference between the number of yeast with the pH and body weight of bali cattle.